ChemInform Abstract: An Efficient and Environmental Benign Synthesis of 2‐Benzimidazoles and 2‐Benzothiazoles Using CeCl3‐NaI as Catalyst. Issue 29 (1st July 2013) - Zhu, Xun; Wei, Yunyang
Abstract The referred procedure should be practicable for the formation of 2‐substituted benzimidazoles and benzothiazoles from aliphatic, aromatic, or heteroaromatic aldehydes.